Association between early childhood caries and age and gender specific height, weight and mid upper arm circumference of school children in puducherry- “a comparative study” - Kurian, Jerin; Renganathan, Sajeev; Gurusamy, Kayalvizhi; Shivashankarappa, Prathima Gajula; Mohandoss, Suganya (Biology, Engineering, Medicine and Science Reports)
Background: Caries is an infectious disease that is induced by the diet. Despite its decline in all age groups on a worldwide basis, it is still a serious public health problem in Indian children and its control should be a priority. It has been demonstrated that ECC can gradually reduce the children’s weight, which can be reversed after complete oral rehabilitation. Aim: The purpose of this study was to find out whether there is an association between ECC and age and gender specific height, weight and mid upper arm circumference (muac). Materials and Method: A study was conducted in a total of 450 children belonging to the age group of 4-6 years attending pre schools in Puducherry. Oral health status was assessed by using decayed extractedfilled teeth index (deft). Weight assessment was done using Akai weighing scale and height was measured using height measuring scale, while MUAC was measured using measuring plastic tape. The obtained data was collected and statistically analyzed. Results: Statistically, there was no significant association between height, weight and MUAC when compared with ECC (p=0.946,0.955,0.909) respectively. No Significant association was found when gender and ECC were compared (males p=0.222) (females p=0.272),but girls were found to be more prone to ECC than boys. Conclusion: In our study, we found that there was no significant association between early childhood caries and age. When gender was compared with ECC, a significant association was found stating that girls are more prone to ECC than males. Overall, When ECC was compared with age and gender specific height, weight and MUAC, there was no significant association found.
Keywords: Early childhood caries; Height; Weight; Mid upper arm circumference; Socio economic status